Análise da tomada de decisão tática de coordenadores de curso de graduação de uma instituição de ensino superior comunitária no Brasil - Bugallo, Eduardo (2024)
Objective: This study aims to analyze the tactical decision-making environment of undergraduate course coordinators from a Brazilian community university, considering the role of these decision-makers. Method: A case study was applied, with data collected through documentary research and focus groups. The data were analyzed using the content analysis technique. Results: The results showed that these decision-makers are exposed to a complex and heterogeneous tactical environment, relying on quality information, knowledge, and repertoire to qualify their decisions. However, they lack symmetrical, customized, friendly, and agile information to qualify their decisions. Conclusion: We identified that the institutional context requires managers to make decisions with scarce deadlines and resources, contrasting with the complexity of the environment that guides this process. Therefore, it is necessary for the university to provide an information system based on organizational processes, aligned with strategic management.